2017
DOI: 10.19027/jai.16.2.124-135
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of astaxanthin and vitamin E in feed on the development of gonads white shrimp broodstock Litopenaeus vannamei Boone 1931

Abstract: The quality of white shrimp Litopenaeus vannamei broodstock can be improved through the addition of astaxanthin and vitamin E in the diet. This study aimed to determine the effect of administration of astaxanthin and vitamin E with different doses in the feed on the maturity gonad of prospective Pacific white shrimp broodstock. Supplementation of 0 mg/kg feed astaxanthin + 0 mg/kg feed vitamin E (control/A), 500 mg/kg feed astaxanthin (B), 350 mg/kg feed vitamin E (C), 500 mg/kg feed astaxanthin and 350 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…However, our study showed that dietary VE did not signi cantly affect the GSI of hybrid male abalone. The result was consistent with those of female shrimp (Macrobrachium nipponense) (Li et al, 2018), male Japanese quail (Coturnix coturnix Japonica) (Biswas et al, 2013), white shrimp broodstock (Litopenaeus vannamei) (Maulana et al, 2017) and female brood sh (Clarias batrachus) (Roy and Mollah, 2010). Besides, the range value showed content of VE at 0.1 g/kg was the optimal level for gonad development of abalone.…”
Section: Reproduction Performancesupporting
confidence: 84%
“…However, our study showed that dietary VE did not signi cantly affect the GSI of hybrid male abalone. The result was consistent with those of female shrimp (Macrobrachium nipponense) (Li et al, 2018), male Japanese quail (Coturnix coturnix Japonica) (Biswas et al, 2013), white shrimp broodstock (Litopenaeus vannamei) (Maulana et al, 2017) and female brood sh (Clarias batrachus) (Roy and Mollah, 2010). Besides, the range value showed content of VE at 0.1 g/kg was the optimal level for gonad development of abalone.…”
Section: Reproduction Performancesupporting
confidence: 84%
“…In the case of males, less need for carotenoid in the formation of gametes was observed, although it is essential and can be stimulated by the consumption of astaxanthin precursors (Braga et al, 2013). In female gonads, the presence of developing eggs can influence the amount of pigment, since the deposition of pigments in crustacean eggs is essential for their perfect development (Maulana et al, 2017;Wang et al, 2018). In the case of stomachs, they can serve as a deposition site for body pigment, however previous studies have not addressed the quantification of pigments in gastric tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of Axn [7,35] and LC-PUFAs [33,36,37] for ovarian development of E. sinensis had been demonstrated in previous studies, their combined effects on E. sinensis remain unclear. Moreover, the combined effects of dietary Axn and LC-PUFAs on crustaceans have been demonstrated in several species, including the hermaphroditic shrimp Lysmata wurdemanni [38], L. vannamei [39], and the giant tiger prawn P. monodon [40]. Considering that DHA is one of the key n-3 LC-PUFAs required for crustacean species as inspired by previous studies, this study was conducted to investigate the combined effect of dietary Axn and DHA on adult female E. sinensis regarding ovarian development, antioxidant capacity, colour parameters, carotenoid concentration, and biochemical composition during the ovarian maturation stage.…”
Section: Introductionmentioning
confidence: 99%